Evaluation of suspected adverse drug reactions of Anti-Diabetic Drugs in a Tertiary Care Hospital for Type II Diabetes Mellitus - Jiji K,; Hemalatha A,; N Rekha,; Sowmya D, (Asian Journal of Pharmaceutical Research and Development, 2025)
Background and Objective: The objective of the study was to evaluate and analyze ADRs in type II diabetic patients and to determine the causality, severity and preventability of reactions. Methods: 150 diabetic patients on anti-diabetic drugs were evaluated prospectively over a period of three months. All patients were observed for ADRs which were then evaluated for its incidence, frequency, severity and causality. Causality was categorized according to the scores obtained from WHO-UMC scale and Naranjo scale. Results and Discussion: A total of 22 ADRs were reported from 150 patients during the study period with female predominance over male. The biguanides class of drugs was responsible for causing the majority of ADRs while the GI system was the most affected organ system. Among the outcomes of 22 ADRs 17 were recovered 5 reactions still continued and there were no fatal evidence. The suspected ADRs were assessed for their causality, it was revealed that 19 were probable and 3 were possible and as per Naranjo scale 20 were probable and 2 possible. Conclusion: These study results provide insight to the healthcare providers on the importance of monitoring and reporting ADR associated with the drug.